Effect of immersion in green tea (camellia sinensis) solution on the transverse strength of heat cured acrylic resin base - Rizky Amalia; Eri Hendra Jubhari (Indonesian Journal of Prosthodontic, 2024)
Objective: To determine the effect of tea solution on the transverse strength of heat cured acrylic resin base. Methods: This study was a laboratory experimental study with post test only with control group design using plate-shaped heat cured acrylic resin samples with a size of 65 mm × 10 mm × 2,5 mm as many as 24 samples. These samples were divided into 6 groups, namely 3 treatment groups immersed in green tea soluble for 3 days, 5 days, and 8 days, and 3 control groups immersed in artificial saliva for 3 days, 5 days, and 8 days. The transverse strength of each group was measured using a Universal Testing Machine (Galdabini). The results were analyzed by Two Way ANOVA test and LSD test. Results: The results of the Two-Way ANOVA test showed a significant difference between immersion in artificial saliva and green tea solution, namely p = 0,000 (p < 0,05). LSD test results showed significant differences between the three immersion duration groups. Between immersion for 3 and 8 days and immersion for 5 and 8 days, the probability value of p = 0,000 (p < 0,05) was obtained. While between immersion for 3 and 5 days, the probability value of p = 0,001 (p < 0,05) was obtained. Conclusion: There is an effect of soaking in green tea solution on the transverse strength of heat cured acrylic resin bases.